What will consumers pay more for? Luxury markets and premium pricing - Yeoman, Ian (Henry Stewart Talks, 2009)
What luxury was, Luxury: materialism, enrichment and time, Perception of luxury in Great Britain and Russia, What will consumers pay more for?, Bling endurance, Attitudes towards individualism, Ethical consumption, Health and wellbeing, Design and nostalgia, Authenticity, The new 'exclusivist' experience, Happynomics, Luxury for rent, Sexuality